Molding resin composition and electronic component device
Patent Information
- Application Number
- JP2021069246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-12-11
Smart Images

Figure 0007651926000001 
Figure 0007651926000002 
Figure 0007651926000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a molding resin composition and an electronic component device. [Background technology]
[0002] In recent years, with the demand for electronic devices to have higher functionality and to be lighter, thinner, shorter, and smaller, the integration and mounting of electronic components has become more and more dense, and the semiconductor packages used in these electronic devices are becoming smaller and smaller than ever before.Furthermore, the radio waves used for communication in electronic devices are becoming higher in frequency.
[0003] 2. Description of the Related Art From the viewpoint of miniaturization of semiconductor packages and compatibility with high frequencies, high dielectric constant epoxy resin compositions for use in sealing semiconductor elements have been proposed (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-036410 A [Patent Document 2] JP 2017-057268 A [Patent Document 3] JP 2018-141052 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, with the miniaturization and high functionality of semiconductor packages (PKG), the development of antenna-in-package (AiP), which is a PKG with an antenna function, is also underway. Examples of materials for sealing antennas include molding resin compositions containing a curable resin, a curing agent, and an inorganic filler. By using a composition that can produce a cured product with a high dielectric constant as the molding resin composition, it is possible to miniaturize the AiP.
[0006] On the other hand, materials with high dielectric constants generally have high dielectric loss tangents. When materials with high dielectric loss tangents are used, the transmission signal is converted to heat due to transmission loss, and communication efficiency is likely to decrease. Here, the amount of transmission loss caused by the radio waves transmitted for communication being converted to heat in the dielectric is expressed as the product of the frequency, the square root of the relative dielectric constant, and the dielectric loss tangent. In other words, the transmission signal is more likely to be converted to heat in proportion to the frequency. And, especially in AiP, the radio waves used for communication are becoming higher in frequency to accommodate the increase in the number of channels accompanying the diversification of information. Therefore, in the molding resin composition, it is required that the cured product after molding has both a high dielectric constant and a low dielectric loss tangent.
[0007] In addition, a material with a high dielectric constant may reduce the fluidity of the molding resin composition. If the molding resin composition has low fluidity, the moldability may be reduced, and the cured product may have poor appearance such as flow marks on the surface after molding. Therefore, the molding resin composition is also required to have good moldability.
[0008] An object of the present disclosure is to provide a molding resin composition that has good moldability and achieves both a high dielectric constant and a low dielectric tangent in a cured product after molding, and an electronic component device using the same. [Means for solving the problem]
[0009] Specific means for solving the above problems include the following aspects. <1> Epoxy resin, A hardener; an inorganic filler containing at least one selected from the group consisting of calcium titanate particles and strontium titanate particles, wherein the total content of the calcium titanate particles and the strontium titanate particles is 30% by volume or more and less than 60% by volume with respect to the entire inorganic filler; A molding resin composition comprising: <2> The curing agent includes an active ester compound. <1> The molding resin composition according to claim 1. <3> The inorganic filler further contains at least one selected from the group consisting of silica particles and alumina particles. <1> or <2> The molding resin composition according to claim 1. <4> The inorganic filler contains alumina particles. <3> The molding resin composition according to claim 1. <5> The relative dielectric constant of the entire inorganic filler at 10 GHz is 80 or less. <1> ~ <4> 10. The molding resin composition according to claim 9, <6> The total content of the inorganic filler is 40% by volume to 85% by volume based on the total molding resin composition. <1> ~ <5> 10. The molding resin composition according to claim 9, <7> Used in high frequency devices, <1> ~ <6> 10. The molding resin composition according to claim 9, <8> Used for antenna-in-package, <1> ~ <7> 10. The molding resin composition according to claim 9, <9> A support member; an electronic component disposed on the support member; The electronic components are sealed. <1> ~ <8> A cured product of the molding resin composition according to any one of the above items, An electronic component device comprising: <10> The electronic component includes an antenna. <9> The electronic component device according to claim 1 . Effect of the Invention
[0010] According to the present disclosure, there are provided a molding resin composition which has good moldability and which, after molding and curing, achieves both a high dielectric constant and a low dielectric tangent, and an electronic component device using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.
[0012] Hereinafter, the embodiments for carrying out the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values and their ranges, and do not limit the present disclosure.
[0013] <Molding resin composition> A molding resin composition according to one embodiment of the present invention comprises an epoxy resin, a curing agent, and an inorganic filler containing at least one type selected from the group consisting of calcium titanate particles and strontium titanate particles (hereinafter also referred to as a "specific filler"), wherein the total content of the calcium titanate particles and the strontium titanate particles is 30% by volume or more and less than 60% by volume of the entire inorganic filler.
[0014] As described above, it is required that the molding resin composition has both a high dielectric constant and a low dielectric loss tangent in the cured product after molding. For example, barium titanate is considered as a material that can obtain a high dielectric constant. However, when barium titanate is used, not only the dielectric constant but also the dielectric loss tangent is likely to increase. In contrast, it has been found that when the above-mentioned specific filler is used, the dielectric constant can be increased while the increase in the dielectric loss tangent can be suppressed compared to the case where barium titanate is used. In other words, in this embodiment, it is considered that by including the specific filler, it is possible to achieve both a high dielectric constant and a low dielectric loss tangent in the cured product after molding.
[0015] As described above, moldability is also required for the molding resin composition. However, if the molding resin composition contains a large amount of the specific filler, the specific filler is non-spherical, so that the molding resin composition is difficult to obtain flowability, and therefore, the molding resin composition is difficult to obtain good moldability. In contrast, in the present embodiment, the total content of the specific filler is 30% by volume or more and less than 60% by volume of the total inorganic filler, and therefore, it is considered that the molding resin composition has good flowability and moldability compared to when the total content of the specific filler is higher than the above range. For the reasons described above, it is presumed that the molding resin composition of this embodiment has good moldability and can achieve both a high dielectric constant and a low dielectric loss tangent in the cured product after molding.
[0016] Hereinafter, each component constituting the molding resin composition will be described. The molding resin composition of the present embodiment contains an epoxy resin, a curing agent, and an inorganic filler, and may contain other components as necessary.
[0017] (Epoxy resin) The type of epoxy resin is not particularly limited as long as it has an epoxy group in the molecule.
[0018] Specific examples of epoxy resins include novolac-type epoxy resins (phenol novolac-type epoxy resins, orthocresol novolac-type epoxy resins, etc.) obtained by epoxidizing a novolac resin obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, etc., and naphthol compounds such as α-naphthol, β-naphthol, dihydroxynaphthalene, etc., with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, propionaldehyde, etc., under an acidic catalyst; triphenylmethane-type epoxy resins obtained by epoxidizing a triphenylmethane-type phenolic resin obtained by condensing or co-condensing the above-mentioned phenolic compound with an aromatic aldehyde compound such as benzaldehyde, salicylaldehyde, etc., under an acidic catalyst; and novolac-type epoxy resins obtained by co-condensing the above-mentioned phenolic compound and naphthol compound with an aldehyde compound under an acidic catalyst. Copolymerized epoxy resins obtained by epoxidizing resins; diphenylmethane-type epoxy resins which are diglycidyl ethers of bisphenol A, bisphenol F, etc.; biphenyl-type epoxy resins which are diglycidyl ethers of alkyl-substituted or unsubstituted biphenols; stilbene-type epoxy resins which are diglycidyl ethers of stilbene-based phenolic compounds; sulfur-containing epoxy resins which are diglycidyl ethers of bisphenol S, etc.; epoxy resins which are glycidyl ethers of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester-type epoxy resins which are glycidyl esters of polycarboxylic acids such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidylamine-type epoxy resins in which active hydrogen bonded to nitrogen atoms of aniline, diaminodiphenylmethane, isocyanuric acid, etc. is replaced with a glycidyl group; dicyclopentadiene-type epoxy resins obtained by epoxidizing co-condensation resins of dicyclopentadiene and phenolic compounds;Alicyclic epoxy resins such as vinylcyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane, which are epoxy-modified epoxy resins in which the olefin bonds in the molecule have been epoxidized; paraxylylene-modified epoxy resins, which are glycidyl ethers of paraxylylene-modified phenolic resins; metaxylylene-modified epoxy resins, which are glycidyl ethers of metaxylylene-modified phenolic resins; terpene-modified epoxy resins, which are glycidyl ethers of terpene-modified phenolic resins; and dicyclopentadiene-modified phenolic resins, which are glycidyl ethers of dicyclopentadiene-modified phenolic resins. Examples of the epoxy resin include pentadiene-modified epoxy resins; cyclopentadiene-modified epoxy resins which are glycidyl ethers of cyclopentadiene-modified phenolic resins; polycyclic aromatic ring-modified epoxy resins which are glycidyl ethers of polycyclic aromatic ring-modified phenolic resins; naphthalene-type epoxy resins which are glycidyl ethers of naphthalene ring-containing phenolic resins; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid; aralkyl-type epoxy resins obtained by epoxidizing aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; and the like. Furthermore, epoxy-oxidized acrylic resins and the like can also be mentioned as epoxy resins. These epoxy resins may be used alone or in combination of two or more.;
[0019] The epoxy equivalent of the epoxy resin (molecular weight / number of epoxy groups) is not particularly limited. From the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, the epoxy equivalent of the epoxy resin is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq. The epoxy equivalent of the epoxy resin is a value measured by a method conforming to JIS K 7236:2009.
[0020] When the epoxy resin is solid, the softening point or melting point of the epoxy resin is not particularly limited. The softening point or melting point of the epoxy resin is preferably 40° C. to 180° C. from the viewpoints of moldability and reflow resistance, and more preferably 50° C. to 130° C. from the viewpoint of handleability during preparation of the molding resin composition. The melting point or softening point of the epoxy resin is a value measured by differential scanning calorimetry (DSC) or a method in accordance with JIS K 7234:1986 (ring and ball method).
[0021] The mass proportion of the epoxy resin in the total amount of the molding resin composition is preferably 0.5 mass% to 30 mass%, more preferably 2 mass% to 20 mass%, and even more preferably 3.5 mass% to 13 mass%, from the viewpoints of strength, fluidity, heat resistance, moldability, etc.
[0022] (hardening agent) The molding resin composition in the present embodiment contains a curing agent. The type of the curing agent is not particularly limited.
[0023] The curing agent preferably contains an active ester compound. The active ester compound may be used alone or in combination of two or more. Here, the active ester compound refers to a compound having one or more ester groups in one molecule that react with an epoxy group and has a curing action for an epoxy resin. In addition, when the curing agent contains an active ester compound, the curing agent may contain a curing agent other than the active ester compound, or may not contain a curing agent other than the active ester compound.
[0024] When an active ester compound is used as a curing agent, the dielectric tangent of the cured product can be kept low compared to when a phenolic or amine curing agent is used as a curing agent. The reason for this is presumed to be as follows. In the reaction between an epoxy resin and a phenolic or amine curing agent, a secondary hydroxyl group is generated. In contrast, in the reaction between an epoxy resin and an active ester compound, an ester group is generated instead of a secondary hydroxyl group. Since an ester group has a lower polarity than a secondary hydroxyl group, a molding resin composition containing an active ester compound as a curing agent can reduce the dielectric tangent of the cured product compared to a molding resin composition containing only a curing agent that generates a secondary hydroxyl group as a curing agent. In addition, while polar groups in the cured product increase the water absorption of the cured product, the polar group concentration of the cured product can be reduced by using an active ester compound as a curing agent, and the water absorption of the cured product can be reduced. By reducing the water absorption of the cured product, that is, by reducing the content of H2O, which is a polar molecule, the dielectric tangent of the cured product can be further reduced.
[0025] The type of active ester compound is not particularly limited as long as it has one or more ester groups in the molecule that react with an epoxy group. Examples of active ester compounds include phenol ester compounds, thiophenol ester compounds, N-hydroxyamine ester compounds, and esters of heterocyclic hydroxy compounds.
[0026] Examples of active ester compounds include ester compounds obtained from at least one of an aliphatic carboxylic acid and an aromatic carboxylic acid and at least one of an aliphatic hydroxy compound and an aromatic hydroxy compound. Ester compounds having an aliphatic compound as a polycondensation component tend to have excellent compatibility with epoxy resins due to the presence of an aliphatic chain. Ester compounds having an aromatic compound as a polycondensation component tend to have excellent heat resistance due to the presence of an aromatic ring.
[0027] Specific examples of active ester compounds include aromatic esters obtained by condensation reaction between aromatic carboxylic acid and phenolic hydroxyl group. Among them, aromatic esters obtained by condensation reaction between aromatic carboxylic acid and phenolic hydroxyl group using a mixture of aromatic carboxylic acid components in which 2 to 4 hydrogen atoms of aromatic rings such as benzene, naphthalene, biphenyl, diphenylpropane, diphenylmethane, diphenylether, and diphenylsulfonic acid are substituted with carboxyl groups, monohydric phenols in which one hydrogen atom of the aromatic ring is substituted with hydroxyl groups, and polyhydric phenols in which 2 to 4 hydrogen atoms of the aromatic ring are substituted with hydroxyl groups as raw materials are preferred. That is, aromatic esters having structural units derived from the aromatic carboxylic acid components, structural units derived from the monohydric phenols, and structural units derived from the polyhydric phenols are preferred.
[0028] A specific example of the active ester compound is an active ester resin having a structure obtained by reacting a phenolic resin having a molecular structure in which a phenolic compound is bonded via an aliphatic cyclic hydrocarbon group with an aromatic dicarboxylic acid or its halide and an aromatic monohydroxy compound, as described in JP 2012-246367 A. As the active ester resin, a compound represented by the following structural formula (1) is preferable.
[0029] [ka]
[0030] In structural formula (1), R 1 represents an alkyl group having 1 to 4 carbon atoms; X represents an unsubstituted benzene ring, an unsubstituted naphthalene ring, a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms, or a biphenyl group; Y represents a benzene ring, a naphthalene ring, or a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms; k is 0 or 1; and n represents the average number of repetitions and is 0.25 to 1.5.
[0031] Specific examples of the compound represented by structural formula (1) include the following exemplary compounds (1-1) to (1-10): In the structural formula, t-Bu is a tert-butyl group.
[0032] [ka]
[0033] [ka]
[0034] Other specific examples of the active ester compound include a compound represented by the following structural formula (2) and a compound represented by the following structural formula (3), which are described in JP2014-114352A.
[0035] [ka]
[0036] In structural formula (2), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms; Z is an ester-forming structural moiety (z1) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or a naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, or a hydrogen atom (z2), and at least one of Z is an ester-forming structural moiety (z1).
[0037] In structural formula (3), R 1 and R 2are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms; Z is an ester-forming structural moiety (z1) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or a naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, or a hydrogen atom (z2), and at least one of Z is an ester-forming structural moiety (z1).
[0038] Specific examples of the compound represented by structural formula (2) include the following exemplary compounds (2-1) to (2-6).
[0039] [ka]
[0040] Specific examples of the compound represented by structural formula (3) include the following exemplary compounds (3-1) to (3-6).
[0041] [ka]
[0042] Commercially available products may be used as the active ester compound. Commercially available products of the active ester compound include "EXB9451", "EXB9460", "EXB9460S", and "HPC-8000-65T" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure; "EXB9416-70BK", "EXB-8", and "EXB-9425" (manufactured by DIC Corporation) as active ester compounds containing an aromatic structure; "DC808" (manufactured by Mitsubishi Chemical Corporation) as active ester compounds containing an acetylated product of phenol novolac; and "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as active ester compounds containing a benzoylated product of phenol novolac.
[0043] The ester equivalent (molecular weight / number of ester groups) of the active ester compound is not particularly limited, and from the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, it is preferably 150 g / eq to 400 g / eq, more preferably 170 g / eq to 300 g / eq, and even more preferably 200 g / eq to 250 g / eq. The ester equivalent of the active ester compound is a value measured by a method in accordance with JIS K 0070:1992.
[0044] From the viewpoint of keeping the dielectric tangent of the cured product low, the equivalent ratio of the epoxy resin to the active ester compound (ester group / epoxy group) is preferably 0.9 or more, more preferably 0.95 or more, and even more preferably 0.97 or more. From the viewpoint of minimizing unreacted active ester compound, the equivalent ratio of the epoxy resin to the active ester compound (ester group / epoxy group) is preferably 1.1 or less, more preferably 1.05 or less, and even more preferably 1.03 or less.
[0045] The curing agent may contain other curing agents other than the active ester compound. The type of other curing agent is not particularly limited and can be selected according to the desired properties of the molding resin composition. Examples of other curing agents include phenol curing agents, amine curing agents, acid anhydride curing agents, polymercaptan curing agents, polyaminoamide curing agents, isocyanate curing agents, and blocked isocyanate curing agents.
[0046] Specific examples of the phenolic curing agent include polyhydric phenolic compounds such as resorcin, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol; novolak-type phenolic resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene, with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde, under an acid catalyst; and polyphenolic compounds synthesized from the above phenolic compounds and dimethoxy-para-xylene, bis(methoxymethyl)biphenyl, or the like. Examples of the phenol curing agent include aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; paraxylylene-modified phenolic resins, metaxylylene-modified phenolic resins; melamine-modified phenolic resins; terpene-modified phenolic resins; dicyclopentadiene-type phenolic resins and dicyclopentadiene-type naphthol resins synthesized by copolymerization of the above-mentioned phenolic compounds and dicyclopentadiene; cyclopentadiene-modified phenolic resins; polycyclic aromatic ring-modified phenolic resins; biphenyl-type phenolic resins; triphenylmethane-type phenolic resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acid catalyst; and phenolic resins obtained by copolymerizing two or more of these. These phenolic curing agents may be used alone or in combination of two or more.
[0047] The functional group equivalent of the other curing agent (hydroxyl group equivalent in the case of a phenolic curing agent) is not particularly limited. From the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, the functional group equivalent of the other curing agent is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq. The functional group equivalent of other curing agents (hydroxyl group equivalent in the case of phenolic curing agents) is a value measured by a method conforming to JIS K 0070:1992.
[0048] The softening point or melting point of the curing agent is not particularly limited. From the viewpoints of moldability and reflow resistance, the softening point or melting point of the curing agent is preferably 40° C. to 180° C., and from the viewpoint of handleability during production of the molding resin composition, it is more preferably 50° C. to 130° C. The melting point or softening point of the curing agent is a value measured in the same manner as the melting point or softening point of the epoxy resin.
[0049] The equivalent ratio of the epoxy resin to the curing agent (all curing agents when multiple types of curing agents are used), i.e., the ratio of the number of functional groups in the curing agent to the number of functional groups in the epoxy resin (number of functional groups in the curing agent / number of functional groups in the epoxy resin) is not particularly limited. From the viewpoint of keeping the unreacted portions of each to a minimum, it is preferably set in the range of 0.5 to 2.0, more preferably in the range of 0.6 to 1.3. From the viewpoint of moldability and reflow resistance, it is even more preferably set in the range of 0.8 to 1.2.
[0050] When the curing agent contains an active ester compound and other curing agents, the mass proportion of the active ester compound in the total amount of the active ester compound and other curing agents is preferably 80 mass % or more, more preferably 85 mass % or more, and even more preferably 90 mass % or more, from the viewpoint of keeping the dielectric tangent of the cured product low.
[0051] When the curing agent contains an active ester compound and another curing agent, the total mass proportion of the epoxy resin and the active ester compound in the total amount of the epoxy resin and the curing agent is preferably 80 mass % or more, more preferably 85 mass % or more, and even more preferably 90 mass % or more, from the viewpoint of keeping the dielectric tangent of the cured product low.
[0052] (Cure accelerator) The molding resin composition in the present embodiment may contain a curing accelerator as necessary. The type of the curing accelerator is not particularly limited and can be selected according to the type of epoxy resin or curing agent, the desired properties of the molding resin composition, and the like.
[0053] Examples of the curing accelerator include diazabicycloalkenes such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, and 2-heptadecylimidazole, derivatives of the cyclic amidine compounds, phenol novolac salts of the cyclic amidine compounds or their derivatives, and combinations of these compounds with maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone. Compounds having intramolecular polarization obtained by adding a compound having a π bond, such as a quinone compound or diazophenylmethane; cyclic amidinium compounds, such as the tetraphenylborate salt of DBU, the tetraphenylborate salt of DBN, the tetraphenylborate salt of 2-ethyl-4-methylimidazole, and the tetraphenylborate salt of N-methylmorpholine; tertiary amine compounds, such as pyridine, triethylamine, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the above tertiary amine compounds; ammonium salt compounds, such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide;Organic phosphines such as primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, and tertiary phosphines such as triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, and tris(benzyl)phosphine; phosphine compounds such as complexes of the organic phosphines and organic borons; and the organic phosphines or the phosphine compounds, which are combined with maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, quinone compounds such as 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone, and the like, and compounds having a π bond such as diazophenylmethane are added to the organic phosphines or the phosphine compounds, and 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-bromophenol, 4-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-bromophenol, 4-bromophenol, 2-bromophenol, 4-bromophenol, 3 ...4-bromophenol, 3-bromophenol, 2-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bromophenol, 4-bromophenol, 3-bro - Compounds having intramolecular polarization obtained by reacting with halogenated phenol compounds such as iodinated phenol, 2-iodinated phenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6-bromo-2-naphthol, and 4-bromo-4'-hydroxybiphenyl, followed by a dehydrohalogenation process;Examples of the tetra-substituted phosphonium include tetra-substituted phosphonium compounds such as tetraphenylphosphonium, tetraphenylborate salts of tetra-substituted phosphonium such as tetraphenylphosphonium tetra-p-tolylborate, and salts of tetra-substituted phosphonium with phenolic compounds; salts of tetraalkylphosphonium with partial hydrolysates of aromatic carboxylic acid anhydrides; phosphobetaine compounds; and adducts of phosphonium compounds with silane compounds. The curing accelerators may be used alone or in combination of two or more. Among these, particularly suitable curing accelerators include triphenylphosphine, an adduct of triphenylphosphine and a quinone compound, an adduct of tributylphosphine and a quinone compound, and an adduct of tri-p-tolylphosphine and a quinone compound.
[0054] When the molding resin composition contains a curing accelerator, the amount is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, per 100 parts by mass of the resin component (total amount of the epoxy resin and the curing agent). When the amount of the curing accelerator is 0.1 parts by mass or more per 100 parts by mass of the resin component, the composition tends to cure well in a short time. When the amount of the curing accelerator is 30 parts by mass or less per 100 parts by mass of the resin component, the curing speed is not too fast and a good molded product tends to be obtained.
[0055] (Inorganic filler) The molding resin composition in this embodiment contains an inorganic filler containing a specific filler (i.e., at least one selected from the group consisting of calcium titanate particles and strontium titanate particles). The total content of the specific filler is 30% by volume or more and less than 60% by volume with respect to the total inorganic filler. In other words, the inorganic filler contains the specific filler and other fillers other than the specific filler.
[0056] -Specific filler- The specific filler may contain only either calcium titanate particles or strontium titanate particles, or may contain both calcium titanate particles and strontium titanate particles. Of these, the specific filler preferably contains calcium titanate particles. The calcium titanate particles and the strontium titanate particles may be surface-treated.
[0057] The total content of the specific filler is 30% by volume or more and less than 60% by volume with respect to the entire inorganic filler. From the viewpoint of obtaining a cured product with a high dielectric constant, the total content of the specific filler is preferably 35% by volume or more and more preferably 40% by volume or more with respect to the entire inorganic filler. From the viewpoint of moldability, the total content of the specific filler is preferably 55% by volume or less and more preferably 50% by volume or less with respect to the entire inorganic filler. And, from the viewpoint of achieving both good moldability and a high dielectric constant of the cured product, the total content of the specific filler is preferably 35% by volume to 55% by volume and more preferably 40% by volume to 50% by volume with respect to the entire inorganic filler.
[0058] The content (vol %) of the specific filler relative to the total inorganic filler can be determined by the following method. A thin sample of the cured product of the molding resin composition is photographed with a scanning electron microscope (SEM). An arbitrary area S is identified in the SEM image, and the total area A of the inorganic filler contained in the area S is determined. Next, a SEM-EDX (energy dispersive X-ray spectrometer) is used to identify the elements of the inorganic filler, thereby determining the total area B of the specific filler contained in the total area A of the inorganic filler. The total area B of the specific filler is divided by the total area A of the inorganic filler to convert it to a percentage (%), and this value is the content (volume %) of calcium titanate particles in the entire inorganic filler. The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, the area S is set to be large enough to contain 100 or more inorganic fillers. The area S may be the total area of a plurality of cut surfaces.
[0059] The total content of the specific filler is preferably 15% by volume or more and less than 40% by volume with respect to the entire molding resin composition. From the viewpoint of obtaining a cured product with a high dielectric constant, the total content of the specific filler is more preferably 25% by volume or more and even more preferably 27% by volume or more with respect to the entire molding resin composition. From the viewpoint of moldability, the total content of the specific filler is more preferably 35% by volume or less and even more preferably 33% by volume or less with respect to the entire molding resin composition. And, from the viewpoint of achieving both good moldability and a high dielectric constant of the cured product, the total content of the specific filler is more preferably 25% by volume to 35% by volume and even more preferably 27% by volume to 33% by volume with respect to the entire molding resin composition.
[0060] The volume average particle size of the specific filler is preferably 0.1 μm to 100 μm, and more preferably 0.5 μm to 30 μm. The volume average particle diameter of the specific filler can be measured as follows. The molding resin composition is placed in a crucible and left at 800°C for 4 hours to be incinerated. The resulting ash is observed with an SEM, separated by shape, and the particle size distribution is obtained from the observed image. From the particle size distribution, the volume average particle diameter of the specific filler can be obtained as the volume average particle diameter (D50). The specific filler may be a mixture of two or more fillers having different volume average particle sizes.
[0061] The shape of the specific filler is not particularly limited, and examples thereof include a spherical shape, an elliptical shape, an irregular shape, etc. The specific filler may be crushed.
[0062] -Other filling materials- The type of the other filler is not particularly limited. Specific examples of the material of the other filler include inorganic materials such as fused silica, crystalline silica, glass, alumina, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, titania, talc, clay, and mica. As other fillers, inorganic fillers having a flame retardant effect may be used, such as aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as a composite hydroxide of magnesium and zinc, and zinc borate. The other fillers may be used alone or in combination of two or more.
[0063] Among these, the other filler preferably contains at least one selected from the group consisting of silica particles and alumina particles, from the viewpoints of being spherical and capable of improving the filling rate, and having a lower dielectric constant than the specific inorganic filler and being able to control the dielectric properties of the composite material. The other filler may contain only either silica particles or alumina particles, or may contain both silica particles and alumina particles. When the other filler contains at least one type selected from the group consisting of silica particles and alumina particles, the total content of the silica particles and alumina particles is preferably 40 volume % to 70 volume %, more preferably 45 volume % to 65 volume %, and even more preferably 50 volume % to 60 volume %, based on the total inorganic filler.
[0064] The other filler preferably contains alumina particles from the viewpoint of increasing the fluidity of the molding resin composition. When the other filler contains alumina particles, the content of the alumina particles is preferably 40 volume % to 70 volume %, more preferably 45 volume % to 65 volume %, and even more preferably 50 volume % to 60 volume %, based on the total volume of the inorganic filler.
[0065] From the viewpoint of keeping the dielectric tangent of the cured product low, the content of barium titanate is preferably less than 10 volume %, more preferably less than 5 volume %, and even more preferably less than 1 volume %, based on the total volume of the inorganic filler.
[0066] The volume average particle diameter of the other filler is not particularly limited. The volume average particle diameter of the other filler is preferably 0.2 μm to 100 μm, more preferably 0.5 μm to 50 μm. When the volume average particle diameter of the other filler is 0.2 μm or more, the increase in viscosity of the molding resin composition tends to be more suppressed. When the volume average particle diameter of the other filler is 100 μm or less, the filling property of the molding resin composition tends to be more improved. The average particle size of the other inorganic fillers is determined by placing the molding resin composition in a crucible and leaving it at 800°C for 4 hours to incinerate it. The resulting ash is observed with an SEM, separated by shape, and the particle size distribution is obtained from the observed image. From the particle size distribution, the volume average particle size (D50) of the other fillers can be obtained. The other filler may be a mixture of two or more fillers having different volume average particle sizes.
[0067] The shape of the other filler is not particularly limited, and examples thereof include a spherical shape, an elliptical shape, an irregular shape, etc. In addition, the other filler may be crushed. The shape of the other fillers is preferably spherical from the viewpoint of improving the flowability of the molding resin composition.
[0068] -Content and characteristics of inorganic fillers as a whole- From the viewpoint of controlling the fluidity and strength of the cured product of the molding resin composition, the total content of the inorganic fillers contained in the molding resin composition is preferably 40 volume % to 90 volume %, more preferably 40 volume % to 85 volume %, even more preferably 45 volume % to 85 volume %, particularly preferably 50 volume % to 82 volume %, and extremely preferably 55 volume % to 80 volume % of the total molding resin composition.
[0069] The content (vol %) of the inorganic filler in the molding resin composition can be determined by the following method. A thin sample of the cured molding resin composition is photographed with a scanning electron microscope (SEM). An arbitrary area S is identified in the SEM image, and the total area A of the inorganic filler contained in the area S is calculated. The total area A of the inorganic filler is divided by the area S and converted into a percentage (%), and this value is the content (volume %) of the inorganic filler in the molding resin composition. The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, the area S is set to be large enough to contain 100 or more inorganic fillers. The area S may be the total area of a plurality of cut surfaces. The inorganic filler may have a biased presence ratio in the direction of gravity when the molding resin composition is cured. In such a case, when imaging with an SEM, the entire cured product in the direction of gravity is imaged, and the area S that includes the entire cured product in the direction of gravity is specified.
[0070] The relative dielectric constant (hereinafter simply referred to as "dielectric constant") of the entire inorganic filler at 10 GHz is, for example, in the range of 80 or less. An example of a method for making the total content of the specific filler 30% by volume or more and less than 60% by volume with respect to the total inorganic filler and making the dielectric constant of the entire inorganic filler 80 or less is to use an unsintered specific filler as the specific filler. Here, the unsintered specific filler refers to a specific filler that has not been exposed to a temperature of 1000° C. or more after synthesis.
[0071] The dielectric constant of the specific filler increases significantly when it is fired at a temperature of 1000° C. or higher. For example, the dielectric constant of unfired calcium titanate after firing at a temperature of 1000° C. for 2 hours is 10 times or more higher than the dielectric constant of calcium titanate before firing. Therefore, when using a sintered specific filler as the specific filler and adjusting the dielectric constant of the entire inorganic filler to 80 or less, the total content of the specific filler relative to the entire inorganic filler is reduced. In addition, in a molding resin composition using an inorganic filler containing a low content of sintered specific filler and having a dielectric constant of 80 or less, a cured product having a high dielectric constant is obtained, but the dielectric constant of the cured product is likely to be uneven. In contrast, in a molding resin composition using an inorganic filler containing an unsintered specific filler at a content of 30% by volume or more and less than 60% by volume and having a dielectric constant of 80 or less, a cured product having a high dielectric constant and high uniformity of the dielectric constant is obtained.
[0072] From the viewpoint of suppressing dielectric loss, the dielectric constant of the entire inorganic filler is preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less. From the viewpoint of miniaturization of electronic components such as antennas, the dielectric constant of the entire inorganic filler is preferably 5 or more, more preferably 10 or more, and even more preferably 15 or more. From the viewpoint of suppressing dielectric loss and miniaturization of electronic components such as antennas, the dielectric constant of the entire inorganic filler is preferably 5 to 50, more preferably 10 to 40, and even more preferably 15 to 30.
[0073] Here, the dielectric constant of the entire inorganic filler is determined, for example, as follows. Specifically, three or more kinds of measurement resin compositions containing the inorganic filler to be measured and a specific curable resin and having different inorganic filler contents, and a measurement resin composition containing the specific curable resin and not containing an inorganic filler are prepared. Examples of the measurement resin composition containing the inorganic filler to be measured and the specific curable resin include a measurement resin composition containing a biphenyl aralkyl type epoxy resin, a phenol curing agent which is a phenol aralkyl type phenol resin, a curing accelerator containing an organic phosphine, and the inorganic filler to be measured. Examples of the measurement resin composition containing three or more different inorganic filler contents include measurement resin compositions having inorganic filler contents of 10 volume%, 20 volume%, and 30 volume% relative to the entire measurement resin composition. Each of the prepared resin compositions for measurement is compression molded under the conditions of a mold temperature of 175°C, molding pressure of 6.9MPa, and curing time of 600 seconds to obtain a cured product for measurement. The dielectric constant of each of the obtained cured products for measurement is measured at 10GHz, and a graph is created in which the content of the inorganic filler is plotted on the horizontal axis and the measured dielectric constant is plotted on the vertical axis. From the obtained graph, a linear approximation is performed by the least squares method, and the dielectric constant when the content of the inorganic filler is 100% by volume is calculated by extrapolation, and this is defined as the "dielectric constant of the entire inorganic filler".
[0074] [Various additives] In addition to the above-mentioned components, the molding resin composition of the present embodiment may contain various additives such as coupling agents, ion exchangers, release agents, flame retardants, colorants, stress relaxation agents, etc. In addition to the additives exemplified below, the molding resin composition of the present embodiment may contain various additives known in the art as necessary.
[0075] (Coupling Agent) The resin composition for molding in this embodiment may contain a coupling agent. From the viewpoint of enhancing the adhesiveness between the resin component and the inorganic filler, it is preferable that the resin composition for molding contains a coupling agent. Examples of the coupling agent include known coupling agents such as silane-based compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, vinyl silane, and disilazane, titanium-based compounds, aluminum chelate-based compounds, and aluminum / zirconium-based compounds.
[0076] When the resin composition for molding contains a coupling agent, the amount of the coupling agent is preferably 0.05 parts by mass to 5 parts by mass, and more preferably 0.1 parts by mass to 2.5 parts by mass with respect to 100 parts by mass of the inorganic filler. When the amount of the coupling agent is 0.05 parts by mass or more with respect to 100 parts by mass of the inorganic filler, the adhesiveness to the frame tends to be further improved. When the amount of the coupling agent is 5 parts by mass or less with respect to 100 parts by mass of the inorganic filler, the moldability of the package tends to be further improved.
[0077] (Ion exchanger) The resin composition for molding in this embodiment may contain an ion exchanger. From the viewpoint of improving the moisture resistance and high-temperature storage characteristics of an electronic component device including an electronic component to be sealed, it is preferable that the resin composition for molding contains an ion exchanger. The ion exchanger is not particularly limited, and conventionally known ones can be used. Specifically, examples include hydrotalcite compounds and hydrated oxides of at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium, and bismuth. The ion exchanger may be used alone or in combination of two or more. Among them, hydrotalcite represented by the following general formula (A) is preferable.
[0078] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O ……(A) (0 < X ≦ 0.5, m is a positive number)
[0079] When the molding resin composition contains an ion exchanger, the content is not particularly limited as long as it is an amount sufficient to capture ions such as halogen ions, etc. For example, the content of the ion exchanger is preferably 0.1 to 30 parts by mass, more preferably 1 to 10 parts by mass, per 100 parts by mass of the resin component (the total amount of the epoxy resin and the curing agent).
[0080] (Release agent) The molding resin composition in this embodiment may contain a mold release agent from the viewpoint of obtaining good releasability from the mold during molding. The mold release agent is not particularly limited, and a conventionally known one may be used. Specific examples include carnauba wax, higher fatty acids such as montanic acid and stearic acid, higher fatty acid metal salts, ester waxes such as montanic acid esters, polyolefin waxes such as oxidized polyethylene and non-oxidized polyethylene, etc. The mold release agent may be used alone or in combination of two or more kinds.
[0081] When the molding resin composition contains a release agent, the amount is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the resin component (total amount of the epoxy resin and the curing agent). When the amount of the release agent is 0.01 parts by mass or more per 100 parts by mass of the resin component, sufficient releasability tends to be obtained. When the amount is 10 parts by mass or less, better adhesion tends to be obtained.
[0082] (Flame retardant) The molding resin composition in this embodiment may contain a flame retardant. The flame retardant is not particularly limited, and a conventionally known flame retardant may be used. Specific examples include organic or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms, metal hydroxides, and the like. The flame retardant may be used alone or in combination of two or more.
[0083] When the molding resin composition contains a flame retardant, the amount is not particularly limited as long as it is an amount sufficient to obtain the desired flame retardant effect. For example, the amount is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, per 100 parts by mass of the resin component (total amount of the epoxy resin and the curing agent).
[0084] (Coloring agent) The molding resin composition in this embodiment may contain a colorant. Examples of the colorant include known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and red iron oxide. The content of the colorant can be appropriately selected depending on the purpose. The colorant may be used alone or in combination of two or more.
[0085] (Stress reliever) The molding resin composition in this embodiment may contain a stress relaxation agent. By containing a stress relaxation agent, it is possible to further reduce the warpage deformation of the package and the occurrence of package cracks. Examples of the stress relaxation agent include known stress relaxation agents (flexible agents) that are generally used. Specific examples include thermoplastic elastomers such as silicone-based, styrene-based, olefin-based, urethane-based, polyester-based, polyether-based, polyamide-based, and polybutadiene-based elastomers, rubber particles such as NR (natural rubber), NBR (acrylonitrile-butadiene rubber), acrylic rubber, urethane rubber, and silicone powder, and rubber particles having a core-shell structure such as methyl methacrylate-styrene-butadiene copolymer (MBS), methyl methacrylate-silicone copolymer, and methyl methacrylate-butyl acrylate copolymer. The stress relaxation agent may be used alone or in combination of two or more types. Among the stress relaxation agents, silicone-based stress relaxation agents are preferred. Examples of silicone-based stress relaxation agents include those having an epoxy group, those having an amino group, and those modified with polyether, and silicone compounds such as silicone compounds having an epoxy group and polyether-based silicone compounds are more preferred.
[0086] When the molding resin composition contains a stress relaxation agent, the amount thereof is, for example, preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, per 100 parts by mass of the resin component (the total amount of the epoxy resin and the curing agent).
[0087] (Method for preparing molding resin composition) The method for preparing the molding resin composition is not particularly limited. A general method includes a method in which a predetermined amount of components is thoroughly mixed with a mixer or the like, then melt-kneaded with a mixing roll, an extruder, or the like, cooled, and pulverized. More specifically, for example, a method in which a predetermined amount of the above-mentioned components is stirred and mixed, kneaded with a kneader, roll, extruder, or the like that has been heated to 70°C to 140°C in advance, cooled, and pulverized can be mentioned.
[0088] The molding resin composition in this embodiment is preferably solid at room temperature and normal pressure (for example, 25°C, atmospheric pressure). When the molding resin composition is solid, the shape is not particularly limited, and examples thereof include powder, granules, tablets, etc. When the molding resin composition is in tablet form, it is preferable that the dimensions and mass of the tablet form are such that they are suitable for the molding conditions of the package, from the viewpoint of handleability.
[0089] (Characteristics of molding resin composition) The cured product obtained by compression molding the molding resin composition of this embodiment under conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 600 seconds has a relative dielectric constant at 10 GHz of, for example, 10 to 20. From the viewpoint of miniaturization of electronic components such as antennas, the relative dielectric constant at 10 GHz of the cured product is preferably 11 to 18, and more preferably 12 to 17. The measurement of the relative dielectric constant is carried out at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, product name "Network Analyzer N5227A").
[0090] The dielectric loss tangent at 10 GHz of the cured product obtained by compression molding the molding resin composition of this embodiment under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 600 seconds is, for example, 0.020 or less. From the viewpoint of reducing transmission loss, the dielectric loss tangent at 10 GHz of the cured product is preferably 0.018 or less, more preferably 0.015 or less. The lower limit of the dielectric loss tangent at 10 GHz of the cured product is not particularly limited, and is, for example, 0.005. The dielectric loss tangent is measured at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, product name "Network Analyzer N5227A").
[0091] When a molding resin composition is molded using a spiral flow measurement mold conforming to EMMI-1-66 under conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds, the flow distance (hereinafter also referred to as "spiral flow") is preferably 80 cm or more, more preferably 100 cm or more, and even more preferably 120 cm or more. The upper limit of the spiral flow is not particularly limited, and may be, for example, 200 cm.
[0092] The gel time of the molding resin composition at 175° C. is preferably 30 to 90 seconds, and more preferably 40 to 60 seconds. The gel time at 175° C. is measured as follows: Specifically, a 3 g sample of the molding resin composition is measured at a temperature of 175° C. using a Curastometer manufactured by JSR Trading Co., Ltd., and the time until the torque curve rises is measured as the gel time (sec).
[0093] (Uses of molding resin composition) The molding resin composition in this embodiment can be used, for example, in the manufacture of electronic component devices, particularly high-frequency devices, which will be described later. The molding resin composition in this embodiment is particularly suitable for use in antenna-in-package (AiP) applications in which an antenna disposed on a support member is encapsulated with the molding resin composition in a high-frequency device.
[0094] <Electronic component equipment> An electronic component device according to one embodiment of the present disclosure includes a support member, an electronic component disposed on the support member, and a cured product of the molding resin composition encapsulating the electronic component. Examples of electronic component devices include those (e.g., high-frequency devices) obtained by mounting electronic components (active elements such as semiconductor chips, transistors, diodes, and thyristors, passive elements such as capacitors, resistors, and coils, antennas, etc.) on a support member such as a lead frame, a pre-wired tape carrier, a wiring board, glass, a silicon wafer, or an organic substrate, and sealing the resulting electronic component region with a molding resin composition.
[0095] The type of the support member is not particularly limited, and any support member that is generally used in the manufacture of electronic component devices can be used. The electronic component may include an antenna, or may include an antenna and an element other than an antenna. The antenna is not limited as long as it functions as an antenna, and may be an antenna element or a wiring.
[0096] In the electronic component device of the present embodiment, if necessary, another electronic component may be disposed on the surface of the support member opposite to the surface on which the electronic component is disposed. The other electronic component may be sealed with the molding resin composition described above, may be sealed with another resin composition, or may not be sealed.
[0097] (Electronic component device manufacturing method) The method for manufacturing an electronic component device according to this embodiment includes the steps of placing an electronic component on a support member and encapsulating the electronic component with the molding resin composition described above. The method for carrying out each of the above steps is not particularly limited and can be carried out by a general method. In addition, the types of the support member and electronic components used in the manufacture of the electronic component device are not particularly limited and support members and electronic components generally used in the manufacture of the electronic component device can be used.
[0098] Methods for encapsulating electronic parts using the above-mentioned molding resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Among these, low-pressure transfer molding is the most common. EXAMPLES
[0099] The above embodiment will be specifically described below using examples, but the scope of the above embodiment is not limited to these examples.
[0100] <Preparation of molding resin composition> Molding resin compositions of Examples and Comparative Examples were prepared by mixing the components shown below in the blending ratios (parts by mass) shown in Tables 1 to 3. This molding resin composition was solid at room temperature and normal pressure. In the table, blank spaces mean that the component is not included. The table also shows the content of inorganic filler relative to the entire molding resin composition ("Total content (volume %)" in the table), the total content of specific filler relative to the entire molding resin composition ("Specific content (volume %)" in the table), the total content of specific filler relative to all inorganic fillers used ("Specific proportion (volume %)" in the table), and the relative dielectric constant at 10 GHz of all inorganic fillers ("Total filler dielectric constant" in the table).
[0101] Epoxy resin 1: Triphenylmethane type epoxy resin, epoxy equivalent 167g / eq (Mitsubishi Chemical Corporation, product name "1032H60") Epoxy resin 2: Biphenyl type epoxy resin, epoxy equivalent 192g / eq (Mitsubishi Chemical Corporation, product name "YX-4000") Epoxy resin 3: o-cresol novolac type epoxy resin, epoxy equivalent 200 g / eq (“N500P” manufactured by DIC Corporation) Epoxy resin 4: Biphenyl aralkyl type epoxy resin, epoxy equivalent 274g / eq (Nippon Kayaku Co., Ltd., product name "NC-3000")
[0102] Hardener 1: Active ester compound, DIC Corporation, product name "EXB-8" Hardener 2: Phenol hardener, phenol aralkyl resin, hydroxyl equivalent 205g / eq (Meiwa Kasei Co., Ltd., product name "MEH7851 series")
[0103] Inorganic filler 1: Calcium titanate particles, unsintered specific filler, volume average particle size: 4 μm, shape: polyhedron Inorganic filler 2: Calcium titanate particles, unsintered specific filler, volume average particle size: 0.2 μm, shape: polyhedron Inorganic filler 3: Strontium titanate particles, unsintered specific filler, volume average particle size: 5 μm, shape: polyhedron Inorganic filler 4: Barium titanate particles, unsintered specific filler, volume average particle size: 6.6 μm, shape: spherical Inorganic filler 5: Alumina particles, other fillers, Volume average particle size: 5.7 μm, Shape: Spherical Inorganic filler 6: Alumina particles, other fillers, Volume average particle size: 0.7 μm, Shape: Spherical Inorganic filler 7: Silica particles, other fillers, volume average particle size: 31 μm, shape: spherical Inorganic filler 8: Silica particles, other fillers, volume average particle size: 6.6 μm, shape: spherical Inorganic filler 9: Silica particles, other fillers, volume average particle size: 0.5 μm, shape: spherical
[0104] Curing accelerator: Triphenylphosphine / 1,4-benzoquinone adduct Coupling agent: N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name "KBM-573") Release agent: Montan acid ester wax (Clariant Japan Co., Ltd., Product name "HW-E") Stress relief agent: Polyether silicone compound (Momentive Performance Materials, product name "SIM768E") Colorant: Carbon black (Mitsubishi Chemical Corporation, product name "MA600")
[0105] The volume average particle size of each of the inorganic fillers is a value obtained by the following measurement. Specifically, first, the inorganic filler was added to a dispersion medium (water) in a range of 0.01% by mass to 0.1% by mass, and dispersed for 5 minutes in a bath-type ultrasonic cleaner. 5 ml of the obtained dispersion was poured into a cell, and the particle size distribution was measured at 25° C. using a laser diffraction / scattering type particle size distribution measuring device (HORIBA, Ltd., LA920). The particle size at an integrated value of 50% (volume basis) in the obtained particle size distribution was defined as the volume average particle size.
[0106] <Evaluation of molding resin composition> (Dielectric constant and dielectric tangent) The molding resin composition was charged into a vacuum hand press and molded under the conditions of a mold temperature of 175°C, molding pressure of 6.9MPa, and curing time of 600 seconds. Post-curing was performed at 175°C for 6 hours to obtain a plate-shaped cured product (length 12.5mm, width 25mm, thickness 0.2mm). This plate-shaped cured product was used as a test piece and the relative dielectric constant and dielectric loss tangent were measured at 25±3°C and 10GHz using a dielectric constant measuring device (Agilent Technologies, product name "Network Analyzer N5227A"). The results are shown in the table ("Relative Dielectric Constant" and "Dielectric Loss Tangent" in the table).
[0107] (Fluidity: Spiral flow) Using a spiral flow measurement mold conforming to EMMI-1-66, the molding resin composition was molded under the conditions of a mold temperature of 180°C, molding pressure of 6.9 MPa, and curing time of 120 seconds, and the flow distance (cm) was measured. The results are shown in the table ("Flow distance (cm)" in the table).
[0108] (Gel Time) Measurement was performed at 175° C. using 3 g of the molding resin composition using a Curelastometer manufactured by JSR Trading Co., Ltd., and the time until the torque curve rose was taken as the gel time (seconds). The results are shown in the table ("Gel time (seconds)" in the table).
[0109] (Moldability) The moldability was evaluated as follows. Specifically, the molding resin composition was molded into a 0.5 mm thick molded product using an Apic Yamada Press (G-Line Press) under conditions of 180°C, 6.9 MPa, and 90 seconds. The molded product was visually inspected for flow marks. The evaluation criteria were as follows. The results are shown in the table. A: No visible flow marks B: Flow marks with slight differences in color were observed in an area less than 1 / 3 of the molded product from the air vent. C: Flow marks occur in an area less than 1 / 3 of the molded product from the air vent. D: Flow marks occur in an area extending from the air vent to more than 1 / 3 of the molded product.
[0110] [Table 1]
[0111] [Table 2]
[0112] [Table 3]
[0113] As shown in the table, the molding resin compositions of the Examples maintain a longer flow distance and have good moldability, while achieving both a high relative dielectric constant and a low dielectric tangent in the cured product after molding, compared to the molding resin compositions of the Comparative Examples.
Claims
1. Epoxy resin, A hardener; an inorganic filler containing calcium titanate particles, the total content of the calcium titanate particles and the strontium titanate particles being 30% by volume or more and less than 60% by volume with respect to the entire inorganic filler; Including, The inorganic filler further contains at least one selected from the group consisting of silica particles and alumina particles, The total content of the inorganic filler is 40% by volume to 85% by volume based on the total molding resin composition, The molding resin composition has a total content of the silica particles and the alumina particles of 40% by volume to 70% by volume based on the total volume of the inorganic filler.
2. The molding resin composition according to claim 1 , wherein the curing agent comprises an active ester compound.
3. The molding resin composition according to claim 1 , wherein the inorganic filler contains alumina particles.
4. The molding resin composition described in claim 1, wherein the content of barium titanate is less than 1 volume % relative to the total inorganic filler.
5. The molding resin composition according to any one of claims 1 to 4, wherein the inorganic filler as a whole has a relative dielectric constant of 80 or less at 10 GHz.
6. The molding resin composition according to any one of claims 1 to 5, which is used for a high-frequency device.
7. The molding resin composition according to any one of claims 1 to 6, which is used for an antenna-in-package.
8. A support member; an electronic component disposed on the support member; A cured product of the molding resin composition according to any one of claims 1 to 7 which encapsulates the electronic component; An electronic component device comprising:
9. The electronic component device of claim 8 , wherein the electronic component includes an antenna.
Citation Information
Patent Citations
Epoxy resin for CEM-3 copper-clad plate with low loss
CN107603145A
Epoxy resin composition, epoxy resin varnish, epoxy resin prepreg and multilayer printed wiring board made by using this epoxy resin prepreg as prepreg for bonding
JP1998158472A
High-specific-permittivity b-stage sheet and printed circuit board prepared by using same
JP2001192536A
Resin composition, resin cured product, sheet-shaped resin cured product and laminate
JP2004210941A
Electronic part and multilayer substrate
JP2004221572A